A Look at Returning Teachers - DeAngelis, Karen J. (Education Policy Analysis Archives, 2013)
Research shows that one-quarter to one-third of teachers who leave the profession return, the majority after only a short absence. Though returning teachers can constitute a substantial share of newly hired teachers in schools each year, little is known about them, the factors associated with their decisions to return, or the schools to which they return. In this study, I use a 20-year longitudinal dataset to examine the characteristics of returning teachers as well as the personal, school, and district factors associated with their return both to the profession and to particular schools. In addition, I consider the extent to which returning teachers contribute to the systematic sorting of teachers across schools. Contrary to conventional wisdom, the loss of teachers to attrition from the profession is more likely to be permanent for smaller schools and districts outside of urban and suburban areas. In addition, both personal and job-related factors impact whether and where former teachers return, albeit differently by gender. Interestingly, personal and pecuniary factors in teaching appear to play a greater role than non-pecuniary factors on male leavers’ decisions regarding whether and where to return, whereas personal, pecuniary, and non-pecuniary factors all influence female leavers’ decisions. Finally, the study demonstrates that returning teachers on average reenter schools that are very similar in terms of student and teacher characteristics to those that they left.